Body dissatisfaction and disordered eating in trans people: A systematic review of the literature. (2nd January 2016) - Jones, Bethany Alice; Haycraft, Emma; Murjan, Sarah; Arcelus, Jon
Abstract: Body dissatisfaction plays a prominent role in gender dysphoria. In some individuals body dissatisfaction appears to manifest disordered eating in order to suppress bodily features of natal gender and accentuate features of gender identity. To date, there has been no systematic review of the literature pertaining to body dissatisfaction and disordered eating in trans individuals. Such a review may highlight important implications for clinicians working with trans people. Therefore, the aim was to critically and systematically review the available literature examining body dissatisfaction or disordered eating in a trans population, and also the literature pertaining to how body dissatisfaction and disordered eating are related in trans people. This review found three studies that explored disordered eating in trans people, five studies that explored body image and disordered eating in trans people, and 18 studies that explored body image in trans people. The findings from this review suggest that body dissatisfaction is core to the distress trans people experience and that this dissatisfaction may also put some individuals at risk of developing disordered eating. Additionally, the findings appear to suggest that gender dysphoria treatment is successful at increasing body satisfaction and improving body image. The clinical implications are discussed.